Palbociclib Induces Senescence in Melanoma and Breast Cancer Cells and Leads to Additive Growth Arrest in Combination With Irradiation - Jost, Tina; Heinzerling, Lucie; Fietkau, Rainer; Hecht, Markus; Distel, Luitpold V. (Frontiers in Oncology, 2021)
Introduction: Several kinase inhibitors (KI) bear the potential to act as radiosensitizers. Little is known of radiosensitizing effects of a wide range of other KI like palbociclib, which is approved in ER+ / HER2- metastatic breast cancer. Method: In our study we used healthy donor fibroblasts, breast cancer and skin cancer cells to investigate the influence of a concomitant KI + radiation therapy. Cell death and cell cycle distribution was studied by flow cytometry after Annexin-V/7-AAD and Hoechst staining. Cellular growth arrest was studied in colony forming assays. Furthermore, we used C12-FDG staining (senescence) and mRNA expression analysis (qPCR) to clarify cellular mechanisms. Results: The CDK4/6 inhibitor palbociclib induced a cell cycle arrest in the G0/G1 phase. Cellular toxicity (cell death) was only slightly increased by palbociclib and not enhanced by additional radiotherapy. As main outcome of the colony formation assays, we found cellular growth arrest was induced by palbociclib and improved by radiotherapy in an additive manner. Noticeably, palbociclib treatment clearly induced senescence not only in breast cancer and partly in melanoma cells, but also in healthy fibroblasts. According to these findings, the down-regulation of senescence-related FOXM1 might be an involved mechanism of the senescence-induction potential of palbociclib. Conclusion: The effect on cellular growth arrest of palbociclib and radiotherapy is additive. Palbociclib induces permanent G0/G1 cell cycle arrest by inducing senescence in fibroblasts, breast cancer and melanoma cells. Direct cell death induction is only a minor secondary mechanism of action. Concomitant KI and radiotherapy is a strategy worth studying in clinical trials.